The gift of dialogue. Its conditions of possibility - Torralba Roselló, Francesc (Church, Communication and Culture, 2025)
The aim of this article is to tackle the conditions of possibility for dialogue. In a social, political, and religious context characterised by polarisation and a certain tendency to Manicheism, it is essential to identify the philosophical foundations of dialogue. This article particularly deals with the dialogue between believers and non-believers understood as mutual learning.